(untitled) (Texas Journal of Medical Science, 2023)
Orthodontics is a specialized branch of dentistry that focuses on diagnosing and correcting irregularities in tooth and jaw alignment. Over the years, there have been significant advancements in the methods used to diagnose orthodontic patients. Modern orthodontic practices now rely on a variety of approaches to ensure accurate diagnoses. This article explores these modern views on the diagnosis of orthodontic patients